Spectrum licensing, policy instruments and market entry - Gary Madden; Erik Bohlin; Thien Tran; Aaron Morey (International Telecommunications Society (ITS), 2013)
Competition policy attempts to address the potential for market failure by encouraging competition in service markets. Often, in wireless communication service markets, national regulatory authorities seek to encourage entry via the spectrum assignment process. Instruments used include the assignment mode (auction or beauty contest), setting aside licenses and providing bidding (price and quantity) credits for potential entrants, and making more licenses (spectrum blocks) available than incumbent firms (excess licenses). The empirical analysis assesses the effectiveness of these policy instruments on encouraging entry. The econometric results show that the probability of entry is enhanced by using auction assignments and excess licenses. Furthermore, quantity, but not price, concessions encourage entry.
Keywords: D82; L51; L96; 330; spectrum licensing; policy instruments; market entry